The Impact of Grazing and Land Reclamation on Natural Plant Biodiversity in Al-Fara’a Area - Ammar Gazi Mahmoud Salahat (My University, 2007)
This study was carried out in Tallouza village which located in the Wadi El-Far’a area in West Bank in order to study the effect of grazing and land reclamation on natural vegetation diversity during two growing seasons (2005-2006 and 2006-2007). Four sites of grassland ecosystem of different type of land use (reclaimed grassland, recently no-grazing grassland, under-grazing grassland, natural reserved grassland) were selected. Vegetation and soil sampling were carried out in mid-April for each growing season, data about amount and distribution of rainfall and temperature were collected for the area during the two growing season. Vegetation sampling and above ground biomasses were determined by using quadrate method. Braun-Blanquet scale was used to visually estimate the relative vegetation cover of each species. The study showed that vegetation composition and percent vegetation cover differ between the sites. Percent vegetation cover was significantly increased in recently no-grazing grassland when compared it with under-grazing grassland and the highest percent vegetation cover was in the natural reserved grassland, and this was indicator for the high potential of this grassland for the rehabilitation in few years when we exclude grazing. Species diversity, evenness, above ground biomass and density were significantly higher in the recently no-grazing grassland and natural reserved grassland than under-grazing grassland. Agricultural activities, especially ploughing were justifying the low natural species diversity evenness, above ground biomass and density in reclaimed grassland. Species found in under-grazing grassland were mostly low palatable to grazing animals, mostly small, prostrate or rosette plants while in natural reserve grassland mostly palatable to grazing animals, mostly tall and erect plants. The vegetation cover observed in mid April 2007 was higher than mid April 2006 at natural reserve grassland and recently no-grazing grassland were due to the differences in distribution of precipitation in the two growing seasons and grazing exclusion. There was no significant difference between the sites in the edaphic factors, so we didn’t know the effect of these factors on natural vegetation diversity in the area.

تم أجراء هذه الدراسة في قرية طلوزة الواقعة في منطقة وادي الفارعة في الضفة الغربية, و ذلك من أجل دراسة اثر الرعي و استصلاح الأراضي على تنوع الغطاء النباتي البري, تمت هذه الدراسة خلال موسمين نمو ) ( 2005-2006, 2006-2007. تم تصميم التجربة في منطقة عشبية, حيث تم اختيار اربعة مواقع, وهذه المواقع هي: أرض عشبية تم استصلاحها, أرض عشبية كانت معرضة للرعي لسنين مضت وفي عام 2005 تم حمايتها من الرعي و أي نشاط زراعي, أرض عشبية كانت و ما زالت تتعرض الرعي, و أرض عشبية تم حمايتها من الرعي وأي نشاط زراعي منذ خمس سنوات مضت. تم أخذ عينات التربة و العينات النباتية في منتصف شهر نيسان لكل موسم نمو وتم جمع معلومات عن توزيع كميات الأمطار و درجات الحرارة خلال الموسمين, حيث تم استخدام طريقة المربع في أخذ العينة النباتية, وتم اتباع مقياس Braun-Blanquet لتقدير نسبة الغطاء النباتي بالعين. لوحظ أثناء الدراسة اختلاف مكونات الغطاء النباتي في مواقع الدراسة وكذلك لوحظ اختلاف نسبة الغطاء النباتي حيث أن نسبة الغطاء النباتي ارتفعت في الأرض التي تمت حمايتها عن نسبته في الأرض التي تتعرض للرعي وأعلى نسبة للغطاء النباتي كانت في الأرض المحمية منذ خمس سنوات و هذا مؤشر على قابلية هذه المراعي للتأهيل في فترة قليلة من الزمن عند منع الرعي. كذلك تنوع النباتات البرية و كثافتها و الكتلة الحيوية كانوا أعلى بشكل معنوي في الأرض المحمية من الرعي و أي نشاط زراعي منذ فترة خمس سنوات و الأرض المحمية حديثا عن الأرض التي تتعرض للرعي.
أثر الرعي و إستصلاح الأراضي على تنوع الغطاء النباتي البري في منطقة الفارعة